Microencapsulation of a Natural Antioxidant from Coffee - Chlorogenic Acid (3-Caffeoylquinic Acid) - Bruna Gonçalves (2017)
Chlorogenic acids, the main polyphenolic group present in coffee, which include the caffeoylquinic acids, are recognized as antioxidants with growing interest in pharmacological, cosmetic, and food applications. However, they can be easily oxidized and they are also very unstable when exposed to high temperatures. Therefore, they can suffer transesterification reactions during storage or food processing, limiting their applications. Nevertheless, this situation can be overcome or minimized by microencapsulation. The purpose of the present study was to prepare by a spray-drying process sodium alginate and modified chitosan microparticles with chlorogenic acid (3-CQA), characterize them (morphological analysis), and evaluate the release profile of 3- CQA from the microparticles in in vitro studies. Furthermore, their antioxidant activity and moisture content were determined. The results address the success of chlorogenic acid microencapsulation, resulting in stable microparticles with controlled release properties and good antioxidant activity, suggesting increasing applications in food and pharmaceutical industry.